IN THE HISTORY OF DECOLONIAL EDUCATION: PAULO FREIRE IN THE SOUTH. UTOPIA IN PRAXIS ON THE CENTENARY OF ITS BIRTH (Isagoge - Journal of Humanities and Social Sciences, 2023)
It is about the review of a book related to Sentithinking Transphilosophy entitled: in the history of decolonial education: Paulo Freire in the South. Utopia in praxis on the centenary of his birth